Spatiotemporal characteristics of atrial fibrillation electrograms: A novel marker for arrhythmia stability and termination. Issue 1 (27th July 2016) - Thanigaimani, Shivshankar; Brooks, Anthony G.; Kuklik, Pawel; Twomey, Darragh J.; Franklin, Samantha; Noschka, Erik; Chapman, Darius; Pathak, Rajeev K.; Mahajan, Rajiv; Sanders, Prashanthan; Lau, Dennis H.
Abstract: Background: Sequentially mapped complex fractionated atrial electrograms (CFAE) and dominant frequency (DF) sites have been targeted during catheter ablation for atrial fibrillation (AF). However, these strategies have yielded variable success and have not been shown to correlate consistently with AF dynamics. Here, we evaluated whether the spatiotemporal stability of CFAE and DF may be a better marker of AF sustenance and termination. Methods: Eighteen sheep with 12 weeks of "one‐kidney, one‐clip" hypertension underwent open‐chest studies. A total of 42 self‐terminating (28–100 s) and 6 sustained (>15 min) AF episodes were mapped using a custom epicardial plaque and analyzed in 4‐s epochs for CFAE, using the NavX CFE‐m algorithm, and DF, using a Fast Fourier Transform. The spatiotemporal stability index (STSI) was calculated using the intraclass correlation coefficient of consecutive AF epochs. Results: A total of 67, 733 AF epochs were analyzed. During AF initiation, mean CFE‐m and the STSI of CFE‐m/DF were similar between sustained and self‐terminating episodes, although median DF was higher in sustained AF ( p =0.001). During sustained AF, the STSI of CFE‐m increased significantly ( p =0.02), whereas mean CFE‐m ( p =0.5), median DF ( p =0.07), and the STSI of DF remained unchanged ( p =0.5). Prior to AF termination, the STSI of CFE‐m was significantly lower ( p <0.001), with a physiologically non‐significant decrease in median DF (−0.3 Hz, p =0.006) and no significant changes in mean CFE‐m ( p =0.14) or the STSI of DF ( p =0.06). Conclusions: Spatiotemporal stabilization of CFAE favors AF sustenance and its destabilization heralds AF termination. The STSI of CFE‐m is more representative of AF dynamics than are the STSI of DF, sequential mean CFE‐m, or median DF.